ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PERAWAT PELAKSANA TERHADAP ROTASI RUANG DI RSUD DR. R. GOETENG TAROENADIBRATA PURBALINGGA - Wasis Eko Kurniawan; Refa Teja Muti (Universitas Harapan Bangsa Purwokerto, 2014)
Background: The rotation or rolling has a sense of play or rotate the placement of thestructural and functional than a certain position to other positions specified in a policywhich is compulsary. While the rotation is interpreted as a punishment and proceduresremain in the hospital is still technically there is no explanation about the reason of therotation.Research objectives: to analyze the factors that affect satisfaction of nursesimplementing the rotation of space in hospitals dr. R. Goeteng TaroenadibrataPurbalingga.Research Methods: This type of research used in this study is correlational analitic.Sampling in this study uses total sampling technique using a questionnaire as datacollection tools were distributed to 74 respondents. Analysis of the data used is amultivariate analysis of Logistic Regression. ResearchResults: The results of this study is the third of the factors that memepengaruhirotation space is there a significant effect among the three factors that affect theimplementation of nurse satisfaction in hospitals roatsi space dr. R. GoetengTaroenadibrata Purbalingga (Opportunity to advance p value = 0.018, Colleague pvalue = 0.010, p value working conditions = 0.004). The most dominant factor of therotation of space in hospitals dr. R. Goeteng Taroenadibrata Purbalingga is asignificant opportunity for advancement, where the p value 0.025 <Î± = 0.05. Conclusion:The most dominant factor of the rotation of space in hospitals dr. R. GoetengTaroenadibrata Purbalingga is an opportunity to advance.Key words: Analysis of the factors that affect nurse satisfaction executor, nurseexecutive, the rotation of the space.